Revista de Economía & Administración Julio - Diciembre de 2020 - Henry Daniel Vera-Ramírez; Fernando Torres-Medina; Fredy José Márquez; Henry Duque Sandoval; Paula Andrea Garizado-Román (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2021)
Número completo